THE ASSOCIATION BETWEEN PRENATAL EXPOSURE TO ENGLISH VOWEL-CONSONANT SOUNDS AND SPEECH DELAY AMONG CHILDREN AGED 2–3 YEARS IN THE DASAN TAPEN, GERUNG HEALTH CENTER, WEST LOMBOK - Nur Komarudin; Danul Aristiawan (Journal of Fundus, 2026)
Background: Speech delay is one of the most common developmental disorders in early childhood and may negatively affect children’s communication, social interaction, and academic readiness. Early language stimulation is essential to support optimal speech and language development. Prenatal auditory stimulation has been proposed as a potential early intervention to enhance fetal brain maturation and auditory processing. Exposure to structured English vowel and consonant sounds may improve auditory discrimination and strengthen neural pathways associated with language acquisition.Objective: This study aimed to analyze the relationship between prenatal auditory stimulation using English vowel and consonant sounds and the risk of speech delay in children.Methods: This quantitative study employed an analytical observational design with a cross-sectional approach. The study was conducted in the working area of Dasan Tapen Primary Health Center, Mataram, from January to March 2026. A total of 60 mothers with children aged 24–60 months were selected using purposive sampling. Data were collected using a structured questionnaire on prenatal auditory stimulation and child developmental screening using KPSP/DDST. Data were analyzed using the Chi-square test with a significance level of p < 0.05. Results: Among the respondents, 39 mothers (65.0%) reported providing prenatal auditory stimulation, while 20 children (33.3%) were identified as having speech delay. Statistical analysis revealed a significant relationship between prenatal auditory stimulation and the risk of speech delay (p = 0.012).Conclusion: Prenatal auditory stimulation through English vowel and consonant sounds was significantly associated with a lower risk of speech delay in children and may serve as an effective early preventive strategy to support language development